Alteration of humoral, cellular and cytokine immune response to inactivated influenza vaccine in patients with Sickle Cell Disease - Nagant, Carole; Barbezange, Cyril; Dedeken, Laurence; Besse-Hammer, Tatiana; Thomas, Isabelle; Mahadeb, Bhavna; Efira, André; Ferster, Alice; Corazza, Francis (PloS one, 2019)
Patients suffering from Sickle Cell Disease (SCD) are at increased risk for complications due to influenza virus. Annual influenza vaccination is strongly recommended but few clinical studies have assessed its immunogenicity in individuals with SCD. The aim of this study was to explore the biological efficacy of annual influenza vaccination in SCD patients by characterizing both their humoral and cell-mediated immunity against influenza antigen. We also aimed to investigate these immunological responses among SCD individuals according to their treatment (hydroxyurea (HU), chronic blood transfusions (CT), both HU and CT or none of them). Seventy-two SCD patients (49 receiving HU, 9 on CT, 7 with both and 7 without treatment) and 30 healthy controls were included in the study. All subjects received the tetravalent influenza α-RIX-Tetra® vaccine from the 2016-2017 or 2017-2018 season. Protective anti-influenza HAI titers were obtained for the majority of SCD patients one month after vaccination but seroconversion rates in patient groups were strongly decreased compared to controls. Immune cell counts, particularly cellular memory including memory T and memory B cells, were greatly reduced in SCD individuals. Functional activation assays confirmed a poorer CD8+ T cell memory. We also document an imbalance of cytokines after influenza vaccination in SCD individuals with an INFγ/IL-10 ratio (Th1-type/Treg-type response) significantly lower in the SCD cohort. SCD patients undergoing CT showed altered immune regulation as compared to other treatment subgroups. Altogether, the cytokine imbalance, the high regulatory T cell levels and the low memory lymphocyte subset levels observed in the SCD cohort, namely for those on CT, suggest a poor ability of SCD patients to fight against influenza infection. Nevertheless, our serological data support current clinical practice for annual influenza vaccination, though immunogenicity to other vaccines involving immunological memory might be hampered in SCD patients and should be further investigated.